Socialization of Legal Understanding towards Street Merchants (PKL) who Provide Trading in Locations that are Prohibited From A Progressive Law Enforcement Perspective - Diana Setiawati; Orryza Almira Mauriska (Universitas Muhammadiyah Surakarta, 2023)
Consumers have the right to use services provided by business actors, including the right to security and comfort, including the use of personal data which should be kept confidential by business actors. In fact, based on Decision Number 90/Pdt.sus-BPSK/2021/PN.Mdn. consumers are harmed because their personal data is accessed without permission by the provider, thereby causing losses to consumers. From this description, it can be seen that there is a gap between das sollen and das sein which needs to be analyzed further in this research. This research aims to find out and analyze legal protection for consumers of postpaid providers regarding hacking and use of personal data without permission based on Law Number 27 of 2022 concerning Personal Data Protection and to find out and analyze the legal consequences arising from use of personal data without permission. The legal research method in this research uses normative juridical research to examine norms, principles, theories, doctrines, etc. related to the research problem, with a statutory approach, the data in this research is secondary data with a library data collection method, and analyzed qualitatively. Based on the research results, it can be seen: (1) Consumers can be protected by Law Number 8 of 1999 concerning Consumer Protection regarding legal protection of their rights as consumers, but this results in the failure to fulfill legal protection for personal data. So, in providing legal protection for consumers' personal data, it can be protected by Law Number 27 of 2022 concerning Personal Data Protection; (2) The resulting legal consequences may be subject to legal liability and sanctions, if based on Law Number 27 of 2022 concerning Personal Data Protection they can be imposed in accordance with Article 67.